IMMEDIATE ROOF STABILITY ANALYSIS FOR NEW ROOMAND- PILLAR MINING TECHNOLOGY IN “ESTONIA” MINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
This paper analysis the immediate roof (IR) stability by the deformation criteria for new room-andpillar mining technology with modern machines in “Estonia” mine. The new mining technology based on a blasting method to move from packaged to emulsion explosives, from 2.0 m to 4.0 m boreholes (FRANZ SCHELL machine) and on new undercutting (SMAG machine) method. With such equipped new technology the entry advance rates reached 3.8 m. As a result of such greater advance rates the situations with unsupported room length up to 5.5 m with decreasing the stability of IR can be expected. The analysis of IR stability based on an in-site underground testing by the leaving bench-mark stations and convergence measurements. The main targets of this study to determine the main parameters for supported/unsupported IR deformation in areas with great entry advance rates and risk analysis concept elaboration.